Executing Search Warrants in the Cloud. - Cauthen, John M. (FBI Law Enforcement Bulletin, 2014)
The article reports that the digital evidences are powerful. The investigators are familiar with recognizing items, which contain potential digital evidence. In such cases they can identify a specific physical location where the data is stored, go to the location, seize the data, and analyze it back in the laboratory.